Synthesis and biological evaluation of natural-product-inspired, aminoalkyl-substituted 1-benzopyrans as novel antiplasmodial agents - Uth, Jan-Frederik; Börgel, Frederik; Lehmkuhl, Kirstin; Schepmann, Dirk; Kaiser, Marcel; Jabor, Valquiria A. P.; Nonato, Maria Cristina; Krauth-Siegel, Renate; Schmidt, Thomas J.; Wünsch, Bernhard (Journal of medicinal chemistry, 2021)
Herein, relationships between the structures of 1-aminoethyl-substituted chromenes and their antimalarial activities were thoroughly investigated. At first, the methyl moiety in the side chain was removed to eliminate chirality. The hydrogenation state of the benzopyran system, the position of the phenolic OH moiety, and the distance of the basic amino moiety toward both aromatic rings were varied systematically. 1-Benzopyran-5-ol 8b (IC50 = 10 nM), 1-benzopyran-7-ol 9c (IC50 = 38 nM), and the aminoalcohol 19c (IC50 = 17 nM) displayed antiplasmodial activity with IC50 values below 50 nM. To identify the mechanism of action, inhibition of three key enzymes by 9c was investigated. 9c was not able to reduce the number of Plasmodia in erythrocytes of mice. This low in vivo activity was explained by fast clearance from blood plasma combined with rapid biotransformation of 9c. Three main metabolites of 9c were identified by liquid chromatography-mass spectrometry (LC-MS) methods.